Kajian Kitab Bait Dua Belas Karya Moeh. Noer Waliyullah: Analisis Semiotik - M. Khusna Amal (Jurnal Lektur Keagamaan, 2014)
This article adopts a semiotic analysis of the manuscripts of the Temple of the Twelve or 'Twelve Stanzas' by Moeh Noer. This study suggests two important conclusions. First, the author presents symbols of religious messages. The symbols in the form of numbers and Arabic linguistic system Pegon (read: Arabic- Ngoko Java). In this context, the use of symbols not only represent the author wishes to convey a religious message to the reader, but also illustrates the power strategy of the author in making differentiation of self. Secondly, through the symbolic reproduction, the author reflects on the religious discourse of God, humans, and how to know God (ma'rifatullah). Keywords: Semiotics, Bait Dua Belas, Pegon Arab, Human, God and Ma'rifatullah.